Digital health literacy—a key factor in realizing the value of digital transformation in healthcare - Sarah Wamala Andersson; Marta Pisano Gonzalez (Frontiers in Digital Health)
BackgroundDigital health technologies and AI are transforming healthcare by improving access, optimizing care, and enabling personalized, preventive, and predictive solutions. However, digital health literacy remains a critical barrier, affecting individuals' ability to engage with digital health technologies (DHTs) and limiting progress toward digital health equity.AimsTo propose a framework that captures the complexity of digital health literacy and guides research, and to share key insights from the Improving Digital Empowerment for Active Healthy Living EU project.ResultsWe introduce a conceptual framework that explores digital health literacy's interactions with social determinants, providing a foundation for research, policy, and practice. Insights from the project (Improving Digital Empowerment for Active Healthy Living), involving 14 partners across 10 European countries, offer evidence-based strategies to empower individuals and promote digital inclusion.Concluding remarksTo keep pace with technological advancements, digital health literacy should be integrated into lifelong learning initiatives. Urgent research is needed to inform policies and guide interventions that enhance digital health literacy and ensure equitable digital transformation in healthcare.